Regionalizing Telecommunications Reform in West Africa - World Bank (Washington, DC, 2013)
This report assesses the potential gains from regionalized telecommunications policy in West Africa. The report seeks to assist officials in the Economic Community of West African States (ECOWAS), the West African Telecommunications Regulators Assembly (WATRA) and member states in designing an effective regional regulatory process. To this end, the report: (i) discusses how regional cooperation can overcome national limits in technical expertise, can enhance the capacity of countries credibly to commit to stable regulatory policy, and ultimately can facilitate infrastructure investment in the region; (ii) identifies trade-distorting regulations that inhibit opportunities for regional trade and economic development, and so are good candidates for regional trade negotiations to reduce indirect trade barriers; and (iii) describes substantive elements of a harmonized regional regulatory policy that can deliver immediate performance benefits.